Slender is the thread : tales from a country law office - Caudill, Harry M., 1922-1990 (University Press of Kentucky, 1987)
In a supplement to his The American Language, H.L. Mencken encapsulated the early history of Kentucky: ""What is now Kentucky was the first region beyond the mountains to be settled. Pioneers began to invade it before the Revolution, and by 1782 it had more than 30,000 population. It was originally a part of Virginia, and the effort to organize it as an independent state took a great deal of politicking.""Kentuckian and lawyer Harry M. Caudill grew up in the coal fields of Letcher County. His book Slender is the Thread reflects the history of a state whose citizens had to labor for t.